Interlaced X‐ray diffraction computed tomography. Issue 2 (1st March 2016) - Vamvakeros, Antonios; Jacques, Simon D. M.; Di Michiel, Marco; Senecal, Pierre; Middelkoop, Vesna; Cernik, Robert J.; Beale, Andrew M.
Abstract : A new data‐collection strategy for Xray diffraction computed tomography experiments is presented that allows, post experiment, a choice between temporal and spatial resolution. Abstract : An X‐ray diffraction computed tomography data‐collection strategy that allows, post experiment, a choice between temporal and spatial resolution is reported. This strategy enables time‐resolved studies on comparatively short timescales, or alternatively allows for improved spatial resolution if the system under study, or components within it, appear to be unchanging. The application of the method for studying an Mn–Na–W/SiO2 fixed‐bed reactor in situ is demonstrated. Additionally, the opportunities to improve the data‐collection strategy further, enabling post‐collection tuning between statistical, temporal and spatial resolutions, are discussed. In principle, the interlaced scanning approach can also be applied to other pencil‐beam tomographic techniques, like X‐ray fluorescence computed tomography, X‐ray absorption fine structure computed tomography, pair distribution function computed tomography and tomographic scanning transmission X‐ray microscopy.